1972
DOI: 10.1136/jnnp.35.1.66
|View full text |Cite
|
Sign up to set email alerts
|

Effect of voluntary contraction of the masseter and other muscles upon the masseteric reflex in man

Abstract: S U MM AR Y Experiments were carried out on seven adult subjects in order to establish the relationship between the magnitude of the masseteric reflex and the amount of voluntary activity present in the muscle at the time the reflex was evoked. At the same time, an effort was made to determine whether the magnitude of the reflex could be enhanced by the simultaneous voluntary contraction of muscles other than that being tested (the Jendrassik manoeuvre). The reflex was evoked by applying controlled downward th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
11
0

Year Published

1975
1975
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 13 publications
1
11
0
Order By: Relevance
“…The results of one such series of trials are shown in Fig. 2 (Hannam, 1972). No differences were found when comparing the latency of the responses evoked 24 LOAD COMPENSATION IN HUMAN MASSETER MUSCLES 25 by the motor with those evoked by the hammer.…”
Section: Jaw-jerk Reflexmentioning
confidence: 94%
“…The results of one such series of trials are shown in Fig. 2 (Hannam, 1972). No differences were found when comparing the latency of the responses evoked 24 LOAD COMPENSATION IN HUMAN MASSETER MUSCLES 25 by the motor with those evoked by the hammer.…”
Section: Jaw-jerk Reflexmentioning
confidence: 94%
“…Although this may be significant, it cannot account for all the data scatter observed, in view of the apparently independent variation of masseter and temporal muscle data. A similar deduction may be made from the variability observed by Hannam,8 where the force level was presumably more accurately controlled and where the voluntary force level was always rising, although possibly at different rates, at the moment of stimulation.…”
Section: Stimulus Mis2mentioning
confidence: 61%
“…The amplitude of the first downward deflection of the accelerometer signal was measured. Calibrations: Horizontal:8 ms, Vertical: 50 m/S2 (accelerometer) 015 mV (EMG) zero by clenching on the transducer. Positive and negative full scale deflections of the meter corresponded to +250 g. The dimensions of the transducer determined the jaw position, which was approximately 8 mm open from the position of maximum closure.…”
mentioning
confidence: 99%
“…It has also been termed “jaw jerk”, “masseter reflex”, “temporomasseter reflex”, and “mandibular reflex” (2). The human jaw‐closing muscles are richly endowed with muscle spindles and the spindle afferents make excitatory connections to the motoneurons of jaw‐closing muscles (3). During isometric contraction, the function of the alpha‐motor and fusimotor system can be revealed during different conditions by examination of the jaw‐stretch reflexes in the EMG of the muscle (4).…”
mentioning
confidence: 99%
“…The level of background EMG activity as well as the biting task (1,14) have also been considered to influence the reflex amplitude, however, all these parameters have not been examined in detail with a highly controlled stretch device. The purpose of this study was, therefore, (1) to systematically investigate the influence of methodological parameters (clenching level, ramp time, displacement, biting position, local anesthetics around teeth) on the jaw‐stretch reflex, (2) to study the reproducibility of the jaw‐stretch reflex both within and between sessions, and (3) to provide insight into the mechanisms underlying the excitability of the motoneuron pool.…”
mentioning
confidence: 99%